Trace metal behaviour in estuarine and riverine floodplain soils and sediments: A review - Du Laing, G.; Rinklebe, J.; Vandecasteele, B.; Meers, E.; Tack, F.M.G. (The Science of the total environment, 2009)
This paper reviews the factors affecting trace metal behaviour in estuarine and riverine floodplain soils and sediments. Spatial occurrence of processes affecting metal mobility and availability in floodplains are largely determined by the topography. At the oxic–anoxic interface and in the anoxic layers of floodplain soils, especially redox-sensitive processes occur, which mainly result in the inclusion of metals in precipitates or the dissolution of metal-containing precipitates. Kinetics of these processes are of great importance for these soils as the location of the oxic–anoxic interface is subject to change due to fluctuating water table levels. Other important processes and factors affecting metal mobility in floodplain soils are adsorption/desorption processes, salinity, the presence of organic matter, sulphur and carbonates, pH and plant growth. Many authors report highly significant correlations between cation exchange capacity, clay or organic matter contents and metal contents in floodplain soils. Iron and manganese (hydr)oxides were found to be the main carriers for Cd, Zn and Ni under oxic conditions, whereas the organic fraction was most important for Cu. The mobility and availability of metals in a floodplain soil can be significantly reduced by the formation of metal sulphide precipitates under anoxic conditions. Ascending salinity in the flood water promotes metal desorption from the floodplain soil in the absence of sulphides, hence increases total metal concentrations in the water column. The net effect of the presence of organic matter can either be a decrease or an increase in metal mobility, whereas the presence of carbonates in calcareous floodplain soils or sediments constitutes an effective buffer against a pH decrease. Moreover, carbonates may also directly precipitate metals. Plants can affect the metal mobility in floodplain soils by oxidising their rhizosphere, taking up metals, excreting exudates and stimulating the activity of microbial symbionts in the rhizosphere.